WET DARK FLUID COSMOLOGICAL MODEL IN SAEZ-BALLESTER THEORY . - A. M. Pund (International Journal of Research Science and Management, 2017)
Axially symmetric Bianchi Type-I wet dark fluid cosmological model is obtained in scalar tensor theory of gravitation proposed by Saez and Ballester [1]. Some physical and kinematical properties of the model are discussed.